Gestión Gubernamental del uso del agua con fines de riego en Ecuador - Cercado Damiany, Walter Alejandro (2022)
This document deals with government management of water use for irrigation purposes in Ecuador. It is necessary that water, an essential natural resource, be regulated and controlled efficiently, which leads to its conservation, comprehensive management and recovery of this resource in different phases, forms and conditions, so that its use is taken advantage of. In our country, the Water Regulation and Control Agency (ARCA) is the entity that regulates and controls irrigation water. The conclusions determine that in Ecuador the fresh water destined for irrigation is the main volume used, but it is carried out under inefficient conditions. The deficiency in the management of irrigation water is observed in all the components of the system, from the catchment to the application in the plots; The rural population of our country generates pressure and intervention on the main sources of water and disturbs the elements of the hydrological cycle at the local level, with results such as low flow in the sources and contamination of surface waters, which aggravates availability and quality. of irrigation water for agricultural activities; In our country, the peasant movement claiming access to water has achieved important achievements, such as the creation of irrigation systems, benefiting their communities locally, since they are aware that they can manage, operate water for their purposes, efficiently and communities of Ecuador, despite the fact that the distribution of the irrigation flow is equitable for the farmers who belong to the Irrigation Boards, it is not efficient, since the water ration is assigned equally to each UPA and even to those who do not need , for not having agriculture on their property